Population Challenges for Bangladesh in the Coming Decades - Streatfield, Peter Kim; Karar, Zunaid Ahsan (Journal of Health, Population and Nutrition, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Bangladesh currently has a population approaching 150 million and will add another 100 million before stabilizing, unless fertility can soon drop below replacement level. This level of fertility decline will require a change in marriage patterns, which have been minimal so far, even with increasing female schooling. It would also benefit from a long-awaited shift to long-term contraception. In addition to the consequence of huge population size, the density of population is already five times that of any other âmega' country (>100 million), a very challenging situation for an agricultural society. Most of the future growth will be urban, increasingly in slums. Numbers of young people will not increase, but numbers of older people will increase 10-fold this century, creating a large burden on the health system, especially for chronic illnesses. High density of population means that agricultural land is virtually saturated, with very limited capacity to expand food production. Climate change may have dramatic impacts on agriculture, through flooding and drought resulting from weather changes and geopolitical influences on transborder rivers. Rising sea-levels and consequent salinity will affect crops and require shifts to alternative land use. Serious long-term planÂning is needed for meeting the growing needs of the population, both for distribution and consumption. Key words: Ageing; Age factor; Child survival; Climate change; Family planning; Fertility; Population growth; Urbanization; Bangladesh doi:10.3329/jhpn.v26i3.1894 J Health Popul Nutr 2008 Sept:26(3):261-272